Methadone Maintenance Treatment Discontinuation Among Young People who use Opioids in Vancouver, Canada. (February 2023) - Pilarinos, Andreas; Kwa, Yandi; Joe, Ronald; Dong, Huiru; Grant, Cameron; Fast, Danya; Buxton, Jane Alison; DeBeck, Kora
Objective: Retaining adolescents and young adults (AYA) in medications for opioid use disorder (MOUD), like methadone maintenance treatment (MMT), is critical to reducing toxic drug fatalities. This analysis sought to identify factors associated with MMT discontinuation among AYA. Method: Data were derived from the At-Risk Youth Study, a prospective cohort study of street-involved AYA in Vancouver, Canada, between December 2005 and June 2018. Multivariable extended Cox regression identified factors associated with time to MMT discontinuation among AYA who recently initiated MMT. In subanalysis, multivariable extended Cox regression analysis identified factors associated with time to "actionable" MMT discontinuation, which could be addressed through policy changes. Results: A total of 308 participants reported recent MMT during the study period. Participants were excluded if they reported MMT in the past 6 months at baseline and were retained in MMT ( n  = 94, 30.5%); were missing MMT status data ( n  = 43, 14.0%); or completed an MMT taper ( n  = 11, 3.6%). Of the remaining 160 participants who initiated MMT over the study period, 102 (63.8%) discontinued MMT accounting for 119 unique discontinuation events. In multivariable extended Cox regression, MMT discontinuation was positively associated with recent weekly crystal methamphetamine use (adjusted hazard ratio [AHR] = 1.67, 95% confidence interval [CI]: 1.19 to 2.35), but negatively associated with age of first "hard" drug use (per year older) (AHR = 0.95, 95% CI: 0.90 to 1.00) and female sex (AHR = 0.66, 95% CI: 0.44 to 0.99). In subanalysis, recent weekly crystal methamphetamine use (AHR = 4.61, 95% CI: 1.78 to 11.9) and weekly heroin or fentanyl use (AHR = 3.37, 95% CI: 1.21 to 9.38) were positively associated with "actionable" MMT discontinuation, while older age (AHR = 0.87, 95% CI: 0.76 to 0.99) was negatively associated. Conclusions: Efforts to revise MMT programming; provide access to a range of MOUD, harm reduction, and treatments; and explore coprescribing stimulants to AYA with concurrent stimulant use may improve treatment retention and reduce toxic drug fatalities.